Women Entrepreneurship In Indonesia: Opportunities And Challenges - Aravik, Havis; Hamzani, Achmad Irwan; Khasanah, Nur (Islamic Banking : Jurnal Pemikiran dan Pengembangan Perbankan Syariah, 2025)
Women's entrepreneurship is becoming a significant global phenomenon, with major contributions to economic empowerment, poverty alleviation, and promotion of gender equality. Internationally, women lead around 35% of small and medium-sized enterprises (SMEs) in Asia, with significant increases in income and participation. In Indonesia, women entrepreneurs play an important role in the growth of the SME sector, which accounts for around 60% of Gross Domestic Product (GDP). Policy support, training, and digital technology have expanded opportunities, although challenges such as gender bias, limited access to capital, and social stereotypes remain. This research uses a qualitative approach through a literature study to analyse the opportunities and barriers faced by women entrepreneurs. The results of the analysis show that digital technology and post-pandemic changes in work culture are creating new opportunities, while low digital literacy and access to finance remain key challenges. With the right strategies, women entrepreneurs can become key drivers of inclusive and sustainable economic development in Indonesia.